Mass-wasting deposits in the Domuyo Volcanic Center, northern Neuquén Andes (Argentina): An analysis of the controlling factors - Hurley, María; Colavitto, Bruno; Astort, Ana; Sagripanti, Lucía; Rosselot, Eduardo A.; Folguera, Andrés (Journal of South American earth sciences, 2020)
A high-mobility mass movement deposit was identified along the Turbio river, which drains the north-facing hillslope of the Domuyo Volcano, in the northern Neuquén Andes. Multiple satellite images and aerial photograph images pre- and post-mass movement have been examined to study its general features and to narrow the time window of the event. Results suggest that, in 1997, a volume of approximately 0.8 × 106 m3 of debris slid nearly 10 km descending a vertical range of ~1400 m and covering a minimum area of 1.5 × 105 m2. The 1997 autumn-winter period was characterized by unusually heavy precipitation in the area (the largest value of precipitation registered in the last 30 years), which was related to a major El Niño Southern Oscillation event. We interpret the deposit as a debris flow event that would have emerged from a moraine whose loose sediments would have set into motion in a context of heavy rainfalls. Furthermore, in the vicinities of the Domuyo Volcano, there is a widespread occurrence of rock avalanches, mostly post-glacial in age, recognized and mapped in this work. Their distribution is coincident with recently published InSAR deformation patterns, which, together with seismic and geophysical data, may be indicating that the volcanic edifice has been subject to inflation processes for at least the last four years. Assuming that similar volcanic unrest episodes occurred in the last thousand years, we can speculate that a volcano-tectonic control could have played a role in the development of these rock avalanches. From there, this work shows that, in a deglacial landscape like the one that defines the Domuyo Volcano area, there are different elements that can act on slope instability. This information intends to be used proactively to advance in the hazard evaluation of these catastrophic processes in the northern Neuquén Andes, a zone with increasing agricultural and tourism activities. •Controls acting on slope failure in a deglacial landscape.•Analysis and dating of a debris flow event in the Domuyo Volcano related to intense rainfall.•Rock avalanches accumulated around the Domuyo Volcano linked to volcanic inflation.